ACE2/Angiotensin-(1-7)/Mas Axis and Cardiovascular Regeneration - PR Jarajapu, Yagna; B. Grant, Maria; K. Raizada, Mohan (Current Hypertension Reviews, 2012)
Discovery of angiotensin converting enzyme (ACE)-2 provided a strong impetus for the development of novel therapeutic tools for the treatment of cardiovascular diseases (CVDs). Angiotensin (Ang)-(1-7), the product of ACE2, via activation of Mas receptor elicits cardiovascular protective effects to a large extent by counter-regulating ACE/Ang- II/AT1-receptor axis of renin angiotensin system (RAS). Bone marrow (BM)-derived progenitor cells play an important role in cardiovascular homeostasis. Angiogenic precursor cells (APCs) have received tremendous attention in the recent years for their therapeutic application for treatment of CVDs, where cardiovascular tissue regeneration is the desired outcome. Autologous cell therapy is a better treatment option for patients with cardiovascular complications. However, circulating APCs from these patients are dysfunctional limiting their therapeutic utility. Thus ex vivo modification to restore their regenerative potential is essential to improve outcomes of autologous cell therapies in CVD. Members of both pathological and protective axes of RAS have been identified in one or more types of BM-derived cells. Modulation of the function of APCs by Ang-II or Ang-(1-7) has now been implicated in the pathology and protection of cardiovascular systems, respectively. Thus, novel functions of RAS in the cardiovascular regenerative physiology and pharmacology are being unraveled. Accumulating evidence points to the ACE2/Ang-(1-7)/Mas axis as a promising target for the treatment of CVDs. The major focus of this review is to highlight the protective role of ACE2/Ang-(1-7)/Mas pathway in the reparative function of BM-derived cells for cardiovascular repair and regeneration.
Keywords: ACE2/Ang-(1-7)/Mas receptor